Profiles of autonomic stress responsivity in a sample of justice‐involved youth: Associations with childhood trauma exposure and emotional and behavioral functioning. Issue 2 (17th March 2020) - Lin, Betty; Kidwell, Mallory C.; Kerig, Patricia K.; Crowell, Sheila E.; Fortuna, Anthony J.
Abstract: A limited number of studies have begun to investigate how the coordinated actions of distinct physiological systems may be related to the development of psychopathology. However, the form taken by these patterns of coordination as well as their antecedents and developmental implications remain to be clarified. The Adaptive Calibration Model (ACM) proposes four prototypical patterns of physiological stress responsivity and corresponding behavioral patterns, which are further tied to varying levels of childhood adversity. The current study is among the first to investigate whether patterns of sympathetic and parasympathetic stress responsivity predicted by the ACM generalize to a sample of justice‐involved youth with disproportionately high rates of childhood trauma exposure. Psychophysiological and self‐report data were collected from 822 justice‐involved youth (182 girls) ages 12–19 years. Latent profile analyses yielded five profiles of physiological responsivity that largely corresponded to the patterns proposed by the ACM. Further, these profiles demonstrated predicted associations with self‐reported emotionality and adjustment. Trauma exposure was associated with a lower likelihood of membership in one of the profiles showing blunted physiological responsivity. Our discussion highlights ways in which insights from the ACM may inform understanding about linkages between physiology and adjustment.